Multi-echelon inventory management policies: a case study for a two-echelon supply chain (2020)
Effective multi-echelon inventory management has been widely recognized for minimizing the average total inventory cost by promoting the coordination and cooperation among supply chain members. This paper presents a spreadsheet simulation of the inventory performance and associated costs obtained by developing a multi-echelon control policy in a real-world two-stage supply chain. Our simulation model is based on a supply chain network of a company located in Colombia and Panama. The results indicate an inventory cost reduction without negatively affecting customer service levels.